STUDENT PERCEPTION OF TECHNOLOGY AND OPTIMIZATION OF ITS USE TO IMPROVE ENGLISH LANGUAGE SKILLS - Rahma Ariani Roshadi; Neni Ratnasari (Media Inovasi Pendidikan dan Pembelajaran, 2026)
The pandemic has been a time when technology has emerged as a solution to support education. Various applications that can be installed on the gadget, one by one, appear to offer alternative learning solutions in various fields. However, the using of technology still has not been maximized by most students. By using a survey model “likert”, this study aims to investigate students' perceptions of using technology, to assist learning activities, and to improve their English skills. The survey was conducted on high school students in West Bandung Regency, where as many as 75 students gave responses, to find out how superior technology is in their point of view, and whether they are optimizing its use as high as their awareness of technological prowess.